Akta S206 – Akta Perlembagaan (Pindaan) (No. 2) 1973 & Constitution (Amendment) (No.2) Act 1973 - A, I S (Journal of Malaysian and Comparative Law, 1974)
(1974) 1 (1) JMCL 12 Notes on Legislation Akta S206 – Akta Perlembagaan (Pindaan) (No. 2) 1973 & Constitution (Amendment) (No.2) Act 1973 - I.S.A.